Fiscal policy and the nominal term premium - Roman Horváth; Lóránt Kaszab; Ales Marsal (Magyar Nemzeti Bank, 2019)
We estimate a New Keynesian model on post-war US data with generalised method of moments using either constant or time- varying debt and labor income taxes. We show that accounting for government debt and distortionary taxes help the New Keynesian model match the level of the nominal term premium with a lower relative risk-aversion than typically found in the literature.
Keywords: E13; E31; E43; E44; E62; 330; zero-coupon bond; nominal term premium; balanced budget rule; government debt; income taxation